Szeged index of TUC4C8 (S) nanotube - Iranmanesh A.,; Pakravesh Y., (Utilitas Mathematica, 2008)
A C4C8 net is a trivalent decoration made by alternating C4 and C8. It can cover either a cylinder or a torus. In this paper we compute the Szeged index of TUC4C 8(S) nanotube.